Safe use of radiopharmaceuticals in patients with chronic kidney disease: a systematic review - Nanno Schreuder; Iris de Romijn; Pieter L. Jager; Jos G. W. Kosterink; Eugène P. van Puijenbroek (SpringerOpen, 2021)
Abstract Background Patients with chronic kidney disease (CKD) may need to have their radiopharmaceutical dosage adjusted to prevent adverse effects and poor outcomes, but there are few recommendations on radiopharmaceutical dosing for this group of patients. The aim of this study is to provide an overview of the available information on radiopharmaceutical dose recommendations for patients with CKD. Methods We performed a systematic literature review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We conducted a literature search in the MEDLINE (PubMed) and Embase databases and screened potentially relevant studies using inclusion and exclusion criteria. We independently assessed the included observational studies' methodologies and extracted relevant data. Results Of the 5795 studies first identified, 34 were included in this systematic review. These studies described three radiopharmaceuticals: [131I]sodium iodine, [18F]fludeoxyglucose, and [131I]iobenguane. Twenty-nine studies (85.3%) reported data on patients with CKD stage 5, while only three studies mentioned CKD patients in other stages (8.8%). Conclusion We found no consistent recommendations for radiopharmaceutical dosing in patients with CKD. Although some studies do mention dosing difficulties in patients with CKD, information is available for only a few radiopharmaceuticals, and recommendations are sometimes contradictory. Further research on radiopharmaceutical dosing in patients with CKD is needed to determine whether these patients require specific dosing, especially for therapeutic radiopharmaceuticals where a non-optimised dose may lead to an increased risk of toxicity for non-targeted organs. Including patients with CKD in studies and providing specific information about dosing in these patients should be a priority for the radiopharmaceutical community.